The Effect Of Recruitment And Turnover On The Performance Of Employees In The Transportation Division Of Pt Raf Cahaya Lestari - Jon Edy; Asep Agung Abdul Rohim; Dwi Istiyanto (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the effect of recruitment and turnover on employee performance in the tranportation in the divvision of PT Raf Cahata Lestari. The reserch applied a quantitative approach whit a saturaded sampling technique, in which all employees were taken as respondents. Data were cillected through likert-scale questtionaires.The data were analized usiing multiple linier regression with the help op SPSS. The results show that partially, recruitment does not heve a sinificant effect on employee performance (sig. 0,927 > 0,05), while turnnover has e positive and significant effect (sig. 0,00 < 0,05). Simultaneously, recruitment and turnover signifocsntly influence employee performance, as indicated by an F-value of 16.675 > F_table 3.257. this means that 25,7% of employee performance variation is infuenced by the two variables, while the remaining 74,3% is explained by other factirs beyond this study.